Blending with shellac to improve water resistance of soybean protein isolate film. (6th September 2020) - Zhang, Yinglong; Li, Tong; Zhang, Hong; Zhang, Huajiang; Chi, Yujie; Zhao, Xiaotong; Li, Hanyu; Wen, Yue
Abstract: The study aims to explore a new packaging film which is prepared with soybean protein isolate (SPI) and shellac (SHL) and research the effects of the amount of SHL on the water resistance and analyze the cause. Compared with the SPI film, the water resistance including water vapor permeability, moisture content, water absorption, contact angle, the resistance of mechanical strength and appearance to immersion water of SPI/SHL films were significantly improved. The films were characterized by Fourier transform infrared spectroscopy (FTIR), X‐ray diffraction (XRD), and scanning electron microscope. The microstructure of films has been changed by the addition of SHL because the hydrogen bond was formed between SPI and SHL by the results of FTIR and XRD. All results showed that a dense reticular structure was formed with SPI after adding SHL, which improved the water resistance of the composite films. Practical applications: Shellac (SHL), which is recognized as safe by the U.S. Food and Drug Administration, is a natural animal secretory substance with nontoxic, moisture proof, and other properties. Soybean protein isolate (SPI) film is a kind of biodegradable packaging material, which has been studied because of excellent degradability compared with petroleum synthetic polymer. However, the film made from SPI itself is easily soluble in water, which also has the disadvantage of poor water resistance. Therefore, the purpose of this study is to study the effect of SHL on the properties of SPI/SHL composite films and improve the water resistance of SPI film. Abstract : The addition of shellac can improve the water resistance of the soy protein isolate film, which is the result of hydrogen bonding between shellac and soy protein isolate.